1990
DOI: 10.1002/bjs.1800771034
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy through a 5 cm subcostal incision

Abstract: of the internal opening for treatment of complex fistulae-in-ano. Dis Colon Rectum 1988; 31: 116-18. Morrison JG, Gathright JB Jr, Ray JE, Ferrari BT, Hicks TC, Timmcke AE. Surgical management of anorectal fistulas in 17.Crohn's disease. Dis Colon Rectum 1989; 32: 492-6. Isbister WH. A simple method for the management of anorectal abscess. Ausr N Z J Sury 1987; 10: 7714.18.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 9 publications
1
24
1
Order By: Relevance
“…Dubois and Berthelot described this operation in 1982 (8) and other reports have appeared in the literature since then (1,6,7). Since the view is restricted and the lighting is difficult to focus into the cut depths of the wound special instruments such as the illumi nated stabilizer, ring retractors (5), lighted retrac tor (6), special head lamps (6) and routine use of insulated forceps have been described.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dubois and Berthelot described this operation in 1982 (8) and other reports have appeared in the literature since then (1,6,7). Since the view is restricted and the lighting is difficult to focus into the cut depths of the wound special instruments such as the illumi nated stabilizer, ring retractors (5), lighted retrac tor (6), special head lamps (6) and routine use of insulated forceps have been described.…”
Section: Discussionmentioning
confidence: 97%
“…Open Cholecystectomy (OC) was first performed in 1882 by Carl Langenbuch using a T shaped incision the horizonal line made parallel to the liver margin (1). Since then several incisions for cholecystectomy have been described including the subcostal, midline and paramedian incisions (2).…”
Section: Introductionmentioning
confidence: 99%
“…5 b) Analgesic doses taken by the patient: Group 1 patients because of less pain took less number of analgesic doses as compared to group group 2 patients (Table 5). Goco et al, 6 Reddick et al, 7 and O'Dwyer et al, 8 in their separate studies had reported mean postoperative analgesic doses in each patient as 1, 2 and 4. Baguley.…”
Section: Age (In Yrs)mentioning
confidence: 98%
“…A less used alternative is the performance of the surgery through a small incision of less than 5 em long in the subcostal area. This procedure has been done earlier by different authors, but the procedure is not popular as yet [3]. This could be due to inadequate visualisation deep inside and difficulty of ligating the cystic duct and artery.…”
Section: Introductionmentioning
confidence: 99%